Mathematical modelling of the molybdenum reduction kinetics in Bacillus pumilus strain Lbna - Halmi, Mohd Izuan Effendi; Ahmad, Siti Aqlima; Syed, Mohd. Arif; Shamaan, Nor Aripin; Abd. Shukor, Mohd. Yunus (Hibiscus Publisher, 2014)
Molybdenum, an emerging pollutant, has just recently been demonstrated to be toxic to spermatogenesis in several animal model systems. Hence its removal and studies on the kinetics of removal is very important at a biotechnological point of view. In this work we study the reduction kinetics of a molybdenum-reducing bacterium using kinetic models such as Haldane, Monod, Teissier, Andrews and Noack, Hinshelwood, Moser, Aiba, Webb (Edward), Yano and Koga, Han and Levenspiel and Luong and evaluated the accuracy of the fitted model using statistical analysis such as Root Mean Square (RMSE), adjusted Coefficient of Determination (R2), corrected Akaike Information Criterion (AICc), Bias Factor, Accuracy Factor and F-test. Statistical analysis shows that the best model was Luong with low values for RMSE and AICc, highest adjusted R2 values, F-test and with Bias Factor and Accuracy Factor nearest to unity (1.0). The calculated value for the Luong’s constants qmax, Ks, Sm, and n were 27.303 hr-1, 115.8 mM, 57.83 mM and 1.405, respectively. The true qmax where the gradient for the slope is zero was approximately 3.38 h-1 at 30 mM molybdenum. The results indicate that the exhaustive use of mathematical models provides new understanding of the way molybdenum inhibits production into molybdenum blue in bacterium. This can provide new knowledge on ways to predict progress of molybdenum reduction in the laboratory and during bioremediation works.